2016
DOI: 10.4172/2165-7556.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoe Fit and Moisture Permeability of a Leather Shoe on Shoe Microclimate and Air Exchange

Abstract: The purpose of this study was to investigate effects of shoe fit and moisture permeability of a leather shoe on shoe microclimate and air exchange Three kinds of leather shoe with different fit were compared, whose ball girth were tight fitted: 1E, medium fitted: 2E, loose fitted: 3E. It was also examined the effect of water vapor permeability of a leather shoe which would affect water vapor transfer in a shoe. We compared the artificial leather with the natural leather. Subject trials were carried out with ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The present investigation was carried out using three kinds of leather shoe with different fit were compared; whose ball girth were tight fitted (1E), medium fitted (2E), loose fitted (3E). Theory of fit effect was supported by previous reports of the bellows action [3].…”
supporting
confidence: 72%
“…The present investigation was carried out using three kinds of leather shoe with different fit were compared; whose ball girth were tight fitted (1E), medium fitted (2E), loose fitted (3E). Theory of fit effect was supported by previous reports of the bellows action [3].…”
supporting
confidence: 72%
“…Foot is usually higher than ambient and footwear surface temperature resulting in heat transfer through convective and radiative pathways. It would be expected that during running, convective heat transfer would be high due to increased air flow around the shoe in addition to movement of the foot within the shoe causing a pumping action forcing air into the environment (Havenith et al 1990;Satsumoto et al 2016).…”
Section: Influence Of Shoe Permeability On Foot and Shoe Microclimatementioning
confidence: 99%
“…Although there were no significant differences in sock sweat absorption between shoe conditions, in-shoe relative humidity and in-shoe absolute humidity values were greater for the closed shoe. It is suggested that increased ventilation can be effective in limiting an increase in skin moisture concentration (Ueda et al 2006;Satsumoto et al 2016). As a result, the mesh upper construction of the open shoe resulted in greater ventilation and therefore a reduction in the amount of moisture accumulated within the shoe.…”
Section: Influence Of Shoe Permeability On Foot and Shoe Microclimatementioning
confidence: 99%
“…High convective heat transfer would be expected due to foot movement within the shoe and airflow around the footwear. 23 There was no forced convection around the foot during standing in the current study, and the thermal resistance of the footwear played an important role in in-shoe temperature increase. The training shoes, with a greater thermal resistance, showed higher in-shoe temperature elevations than firefighting boots during standing.…”
Section: Discussionmentioning
confidence: 53%